Exploration on the Role of Transformational Leadership Linkage Psychological Empowerment in Stimulating Employees’ Innovation Behavior in an Uncertain Environment: Based on Entrepreneurship Perspective - Xiaoying Wei; Ying He (Occupational Therapy International)
Employee Innovative Behavior (EIB) in a stable environment is often based on the company’s planned policy orientation and has higher innovation performance under the transactional leadership behavior characterized by task orientation. In an uncertain environment, transformational corporate leadership behaviors will stimulate EIB. The essence of entrepreneurship is innovation. Enterprises provide employees with spiritual support through entrepreneurship, which can generate more effective long-term incentives for employees. From the perspective of entrepreneurship, based on the Uncertainty-Identity Theory (UIT), through the analysis of 287 pairs of valid sample data from 7 companies, it is found that Environmental Uncertainty (EU) has a positive moderating effect on the relationship between Transformational Leadership (TL) and Psychological Empowerment (PE). PE positively promotes EIB. The indirect effect size of PE is 0.2221, 0.3495, and 0.4450 from low to high, respectively. It is inferred that the interaction between TL and EU can positively promote EIB through the mediating effect of PE. The research conclusions expand the boundary conditions of the relationship between TL and EIB and innovatively provide theoretical guidance for the management of EIB from the perspective of entrepreneurship in an uncertain environment.